Psychosocial Consequences of Female Infertility in Iran: A Meta-Analysis - Zarif Golbar Yazdi, Haniye; Aghamohammadian Sharbaf, Hamidreza; Kareshki, Hossein; Amirian, Malihe (Frontiers in Psychiatry, 2020)
Aim: Despite the fact that infertility is not a life-threatening disease, it does influence various aspects of an individual’s life. The aim of this study is to identify psychosocial consequences of infertility in women, based on a meta-analysis of the relevant studies conducted. Methods: To fully investigate the entirety of the studies published concerning the psychological consequences of infertility of women in Iran, the electronic information banks including Comprehensives Human Sciences Portal, Magiran, Scientific Information Database (SID), Noormags, MEDLIB, ScienceDirect, Google Scholar, Medline, and ProQuest were observed. To maximize the comprehensiveness of the search, the list of references used for all the relevant papers found in the search was investigated manually. The evaluation of the content was based on PRISMA principles, while its analysis was according to the CMA Software. Findings: Based on the analysis carried out on 124 quantitative papers, the psychological consequences of infertility in women in Iran can be categorized in 14 main sections: psychological wellbeing (ES = 3.10), adaptation to infertility (ES = 2.71), quality of life (ES = 1.83), depression (ES = 1.80), anxiety (ES = 1.72), marital relationships (ES = 1.37), personality disorders (ES = 1.37), violence (ES = 1.31), social support (ES = 0.90), self-efficacy (ES = 0.90), coping strategies (ES = 0.84), irrational thoughts (ES = 0.77), somatization disorder (ES = 0.65), and sexual dysfunction (ES = 0.55). Conclusion: Concerning the vast psychosocial consequences of women’s infertility, it is necessary to consider the psychological factors in treatment.